A Formative Evaluation with Extension Educators: Exploring Implementation Approaches Using Web-based Methods - Adrienne M. Duke; Shnovia Joy Maxwell Scott (Journal of Human Sciences and Extension, 2017)
The article describes the formative evaluation of a bullying prevention program called Be SAFE from the perspective of Extension educators. Twelve regional and county educators from Family and Child Development and 4-H Youth Development participated in our study. We used a web-based, mixed methods approach, utilizing both Qualtrics, an online survey software platform, and Scopia, a video conferencing application, to collect survey data and do a focus group. The results of the survey show that three activities, Clear Mind, Mud Mind, Take a Stand, and The Relationship Continuum, were perceived as garnering the most participation from students. However, focus group data indicated that while there was often a high level of participation, the subject matter of the curriculum was too advanced for students in the fifth grade and that classroom size affected how well educators could teach lessons. Furthermore, school access was not an implementation challenge, but the amount of days available to implement the full curriculum was sometimes limited. The data collected through this formative evaluation were used to improve implementation efforts. The process outlined in this article can be used as a model to help program leaders who are interested in using web-based tools to evaluate implementation processes.